“If it all goes digital, we’ll have to learn”: facilitators and barriers to uptake of digital health in British South Asians with cardiometabolic disease - Mel Ramasawmy; David Sunkersing; Dan Roland Persson; Lydia Poole; Kiran Patel; Shivali Modha; Madiha Sajid; Paramjit Gill; Fiona Stevenson; Nushrat Khan; Amitava Banerjee (BMC Digital Health, 2024)
Abstract Background Although availability and utilisation of digital health interventions (DHIs) for management of diabetes and cardiovascular disease (“cardiometabolic disease”) have increased, they may exacerbate health inequalities. South Asians have increased cardiometabolic risk, but their experiences of DHIs are poorly investigated and characterised. Objective To explore facilitators and barriers to DHI uptake and use in South Asian individuals in the UK with cardiometabolic disease. Methods Mixed-methods approach encompassing online/face-to-face/individual interviews (n = 45) and survey (n = 100). After informed consent, transcription and coding, we conducted a thematic analysis informed by a guide for understanding inequalities in DHIs to examine perceptions at the individual, healthcare professional, societal and intervention level. Results Participants described an intersection of factors resulting in varied digital skills and confidence within the community, including individual characteristics, awareness, and support. COVID-19 restrictions acted as both a positive (use of online shopping and social media increasing digital confidence) and negative (lack of access to health services) drivers to DHI uptake. Participants made recommendations for improving DHI uptake in the health service and policy area, such as promotion and upskilling through culturally and language-appropriate avenues such as community organisations and outlets. Participants suggested DHI design improvements should focus on literacy, numeracy, accessibility, and cultural appropriateness. Conclusions DHIs have the potential to support South Asian populations in the UK to prevent and manage cardiometabolic disease. To improve their uptake, approaches to their implementation should consider community diversity to provide appropriate promotion, education, and support.